On the AlDub kalye serye phenomenon - a roundtable discussion - Campos, Patrick F. (2016)
Access online through this link: https://www.plarideljournal.org/article/roundtable-discussion-aldub-kalye-serye-phenomenon
Keywords: Romance in television; Mendoza, Maine; Richards, Alden; Eat Bulaga! (Television program)